Metazoan parasites associated with marine mollusks inhabiting the China Seas: a review - Xin Du; Xin Du; Jing Sun; Jing Sun; Huidong Ju; Huidong Ju; Zhen Xu; Xiaoli Tang; Xuedan Fang; Xuedan Fang; Muhammad Saleem Chang; Muhammad Saleem Chang (Frontiers in Marine Science)
Parasites in mollusks are often neglected by humans, while some species were reported to be harmful to economic mollusks and caused production decrease. Metazoan parasites of mollusk studies from the China Seas started relatively later than other countries. To promote long-term studies on the distribution and diversity of metazoan parasites of mollusks from the China Seas, a comprehensive review has been carried out based on the available literature. The purpose of this study was to perform a critical review about the metazoan parasites associated with mollusks that are useful for the discovery of new metazoans. This publication summarizes information on metazoan parasites of Chinese mollusks from 1932 to 2024. The information is presented and contains 128 species of parasites, distributed among the higher taxa as follows: Turbellaria (2 species), Trematoda (34 species), Cestoda (1 species), Annelida (38 species), Arthropoda (48 species), Porifera (2 species), Cnidaria (1 species), and Mollusca (2 species). Many records of parasites not identified to the species level are also included. Collectively, this review provides a synopsis of the known metazoan parasites of mollusks from the China Seas, as well as presents the known relationship between metazoan parasites and the mollusks, which will broaden our knowledge on the metazoan parasites of mollusks. It is important as it highlights the lack of metazoan parasite studies done in the China Seas and the need for more parasite biodiversity work.